2016
DOI: 10.1139/cjc-2016-0308
|View full text |Cite
|
Sign up to set email alerts
|

Extremal pentagonal chains with respect to bond incident degree indices

Abstract: Numerous molecular structure descriptors, which may be used in theoretical chemistry, are the bond incident degree (BID) indices. This study is devoted to establish a general expression for calculating the BID indices of pentagonal chains and to find the extremal (maximal and minimal) values for a variety of BID indices over the certain collection of pentagonal chains with a fixed number of pentagons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Fig. 2: Carbon graphite graph for (3,4) and t = 3. Table 1: Edge partition of CG(m, n) based on degree sum of end vertices of each edge.…”
Section: R a F T 2 Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 2: Carbon graphite graph for (3,4) and t = 3. Table 1: Edge partition of CG(m, n) based on degree sum of end vertices of each edge.…”
Section: R a F T 2 Main Resultsmentioning
confidence: 99%
“…Some applications related to topological indices of molecular graphs are given in 2,3,9,12,13,18,19,23,26,27,28 and also the references therein. The researchers work in the field of chemical graph theory about the topological applications of carbon nanocones, extremal pentagonal chains, tree like polyphenylene, spiro hexagonal systems, polyphenylene dendrimer nanostars, nanostructures, and polyomino chains in 1,[4][5][6]25 . These chemical applications are motivated us to study topological descriptors and compute for some new chemical graphs.…”
mentioning
confidence: 99%
“…In fact, there also exist numerous research results for a general pentachain. For example, Xiao et al [45] studied a connection between the Kekulé structures of pentachains and the Hosoya index of caterpillar trees, and a general expression for calculating the bond incident degree indices of pentachains was established in [46]. Denote by E[Ξ] the expected value of a random variable.…”
Section: Introductionmentioning
confidence: 99%
“…There are lot of research papers related to the GA index of a graph G which can be found in literature, see for example [9] , [10] , [11] . There are plenty of papers outlined the mathematical properties of these four indices, for example one can consults the papers [10] , [12] , [13] , [14] , [15] , [16] , [17] , [18] and the references therein.…”
Section: Introductionmentioning
confidence: 99%